Kits, assemblies and methods for no-tools toilet installation - WALSH JAMES P; JENSEN ROBERT M; DAVID GROVER (2015)
Kits and methods for installing a toilet bowl or assembly without tools are described. The methods and assembly work with an existing flange or can include a standard closet flange configured to receive a flange bolt. The kits and assemblies include a flange bolt wherein the bolt head is configured so as to fit through an opening in a flange so that the bolt head contacts the lower surface of the flange and the end portion of the bolt stem extends upwardly; and a bolt locking knob, wherein the interior surface of the knob is configured so that when the end of the bolt stem is placed within the knob, it contacts the bolt stem in locking engagement and the knob can be hand tightened. The bolts size is coordinated with the size of the locking knobs to eliminate the use of tools on installation.